China's Avant-Garde Fiction : An Anthology - Wang, Jing, 1950- (Book collections on Project MUSE., 1998)
Enriched by the work of a distinguished group of translators, this collection presents an aesthetic experience that may have outraged many revolutionary-minded readers in China, but one that also occupies an important place in the canon of Chinese literature.